Integritas dan Profesionalisme SDM Pada Tata Kelola Keuangan di Sektor Publik dan Swasta - Ramayanto Ramayanto; Siti Mujanah; Abdul Halik (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2025)
This qualitative study, using a Systematic Literature Review (SLR), aims to analyze the role of human resource (HR) integrity and professionalism in supporting good financial governance in the government and private sectors. This study fills the literature gap regarding the relationship between HR quality and financial governance effectiveness amidst the challenges of bureaucracy, digitalization, and cross-sector dynamics. Data sources were obtained from Dimensions and Scopus databases with publications spanning 2015–2024. Inclusion criteria included relevant, reputable scientific articles, published in Indonesian or English, and available in full text. The analysis results indicate that HR integrity contributes to building transparency and accountability, while professionalism supports the implementation of modern financial systems such as Enterprise Resource Planning, an integrated system that manages all financial processes digitally and in an integrated manner, and agile financial management, an adaptive and responsive financial management approach to changes in the organizational environment. Thematic cluster visualization indicates the importance of synergy between HR capacity, oversight systems, and institutional readiness. This study recommends the development of contextual integrity and professionalism measurement instruments, as well as the need for empirical studies on the role of HR in more adaptive, participatory, and sustainable financial governance reforms.